Produção de fitases e proteases fúngicas, aplicação em rações e valores digestíveis pela tilápia-do-nilo - Novelli, Paula Kern [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study was carried out for screening the phytase production using agroindustrial residues as substrate for solid state fermentation (SSF) and several fungal strains. High phytase production was observed for most of the microorganisms studied, as well as very different biochemical characteristics, including activities at specific pH values. The phytases showed very distinct behavior of optimum and stability pH, optimal values of temperature and stability. A. niger showed the higher values of enzyme activity. Lyophilized enzyme produced by A. niger reached 8,575 U/g and yield of 826,096.50 U/Kg of substrate when fermented in wheat bran. Therefore, the substrate as well as the microorganism strain can affect the biochemical character of the enzyme produced. The high phytase activity and very distinct characteristics established, plus the low cost of substrates, make these fungal phytases potential alternatives for biotechnological industry.

Este estudo foi realizado para o rastreio da produção de fitase utilizando resíduos agroindustriais como substrato para fermentação em estado sólido (SSF) e várias cepas fúngicas. A alta produção de fitase foi observada para a maioria dos microrganismos estudados, bem como características muito diferentes actividades bioquímicas, incluindo a valores de pH específicos. As fitases mostrou um comportamento muito distinto de óptimo e estabilidade do pH, os valores ideais de temperatura e estabilidade. A. niger mostrou os maiores valores de atividade enzimática. Enzima liofilizada produzida por A. niger atingiu 8,575 U / g e rendimento de 826,096.50 U / Kg de substrato quando fermentado em farelo de trigo. Portanto, o substrato, bem como a estirpe de microorganismo pode alterar as características bioquímicas da enzima produzida. A alta atividade de fitase e características muito distintas estabelecidas, além do baixo custo de substratos, fazer estes fungos fitases alternativas potenciais para a indústria biotecnológica.
Screening of fungi phytases produced by solid state fermentation with different agricultural by-products as substrate
Keywords: Tilapia (Peixe) - Alimentação e rações; Enzimas - Aplicações industriais; Fermentação; Tilapia